SOCIAL COMPARISON SEBAGAI MODERATOR INTENSITAS PENGGUNAAN INSTAGRAM DENGAN SELF-ESTEEM - Rahma, Lili Mira Julia; Setiasih, Setiasih (Universitas Gunadarma, 2024)
Instagram social media is one of the media that is widely used to carry out social comparisons with other Instagram social media users which can then affect self-esteem. This study aims to determine the relationship between the intensity of Instagram use and self-esteem with social comparison moderators in emerging adulthood. Selection of participants using a quota sampling technique. This research involved 288 students at university